Evaluation of a tertiary and district general hospital menopause service. Issue 1 (March 2021) - Manley, Kristyn M; Hillard, T; Holloway, D; Bruce, D; Rymer, J
Objective: Requests for management of menopausal symptoms and hormone replacement are increasing in the UK. Referrals to specialist clinics have to be balanced with increasing recommendations within the NHS to improve efficiency and patient care. Study design: Retrospective evaluation of clinic records over two months at a district general (Poole Hospital) and tertiary (Guy's Hospital) menopause service. Data on referral origin, reason for referral, interval from referral to review and outcome were collected and compared between trusts. Main outcome measures: To evaluate and compare referrals and outcomes in a tertiary and district general menopause service and provide recommendations for improving efficiency. Results: Most referrals are from primary care but up to 25% are from other specialties. Half of the appointments are new referrals and 95% of women attend. Of the new referrals, 50% have multiple medical comorbidities, 25% a personal or family history of cancer and 25% treatment resistance; 30% have premature ovarian insufficiency. At Guy's Hospital, 30% are reviewed more than 18 weeks after referral, at Poole Hospital this is 6%. Treatment resistance is reported in half of the women reviewed at follow-up. Conclusions: Menopause services review a complex patient population and the majority of referred women have more than one co-morbidity; they require time, specialist knowledge of current treatment options and a multidisciplinary approach. The main barrier to service efficiency is capacity, particularly in population dense areas; cognitive behavioural therapy and non-hormonal methods appear under-utilised in primary care, as do alternative methods of follow-up within the clinics such as telephone and patient-initiated appointments.